Identification of core objectives for teaching sustainable healthcare education. Issue 1 (1st January 2017) - Teherani, Arianne; Nishimura, Holly; Apatira, Latifat; Newman, Thomas; Ryan, Susan
ABSTRACT: Background : Physicians will be called upon to care for patients who bear the burden of disease from the impact of climate change and ecologically irresponsible practices which harm ecosystems and contribute to climate change. However, physicians must recognize the connection between the climate, ecosystems, sustainability, and health and their responsibility and capacity in changing the status quo. Sustainable healthcare education (SHE), defined as education about the impact of climate change and ecosystem alterations on health and the impact of the healthcare industry on the aforementioned, is vital to prevention of adverse health outcomes due to the changing climate and environment. Objective : To systematically determine which and when a set of SHE objectives should be included in the medical education continuum. Design : Fifty-two SHE experts participated in a two-part modified-Delphi study. A survey was developed based on 21 SHE objectives. Respondents rated the importance of each objective and when each objective should be taught. Descriptive statistics and an item-level content validity index (CVI) were used to analyze data. Results : Fifteen of the objectives achieved a content validity index of 78% or greater. The remaining objectives had content validity indices between 58% and 77%. The preclinical years of medical school were rated as the optimal time for introducing 13 and the clinical years for introducing six of the objectives. Respondents noted the definition of environmental sustainability should be learned prior to medical school and identifying ways to improve the environmental sustainability of health systems in post-graduate training. Conclusions : This study proposes SHE objectives for the continuum of medical education. These objectives ensure the identity of the physician includes the requisite awareness and competence to care for patients who experience the impact of climate and environment on health and advocate for sustainability of the health systems in which they work. Abbreviations : CVI: Content validity index; SHE: Sustainable healthcare education